Ojections to population control with particular reference to the Philippines : an ethical response - Justo, Benjamin Alivan, 1940- ([Manila] : South East Asia Graduate School of Theology, 1969)
This research is an attempt to find and present the best Christian response to the perplexing ethical problems that emanate from the effort to control the rapid growth of population. It seeks to achieve this objective by focusing its survey, analysis, and examination on both the major objections to, as well as, the rationale and affirmations to population control.
In partial fulfillment of the requirements for the Degree of Master of Theology
A Thesis submitted to the South East Asia Graduate School of Theology
Thesis (M.Theo.) -South East Asia Graduate School of Theology